Physical Modeling of Structure and Dynamics of Concentrated, Tornado-like Vortices (A Review) - Aleksey Yu. Varaksin; Sergei V. Ryzhkov (Aerospace, 2024)
Physical modeling is essential for developing the theory of concentrated, tornado-like vortices. Physical modeling data are crucial for interpreting real tornado field measurements and mathematical modeling data. This review focuses on describing and analyzing the results of a physical modeling of the structure and dynamics of tornado-like vortices, which are laboratory analogs of the vortex structures observed in nature (such as “dust devils” and air tornadoes). This review discusses studies on various types of concentrated vortices in laboratory conditions: (i) wall-bounded, stationary, and tornado-like vortices, (ii) wall-free, quasi-stationary, and tornado-like vortices, and (iii) wall-free, non-stationary, and tornado-like vortices. In our opinion, further progress in the development of the theory of non-stationary concentrated tornado-like vortices will determine the possibility of setting up the following studies: conducting experiments in order to study the mechanisms of vortex generation near the surface, determining the factors contributing to the stabilization (strengthening) and destabilization (weakening) of the generated vortices, and to find methods and means of controlling vortices.